2018
DOI: 10.1016/j.resuscitation.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with combined do-not-resuscitate and do-not-intubate orders: A retrospective chart review at an urban tertiary care center

Abstract: Compared with DNR orders alone, combined DNR/DNI orders are more strongly associated with many of the same factors that have been linked to DNR orders. Awareness of the extent to which the two directives may be conflated during code status discussions is needed to promote patient-centered application of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The demographic characteristics of the participants are shown in Table 1. The median age of the ICU physician participants was 39 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and 54.5% were female. The primary specialty of the great majority of the ICU physicians was anesthesiology (88.2%), followed by internal medicine (9.9%) and surgery (1.9%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic characteristics of the participants are shown in Table 1. The median age of the ICU physician participants was 39 (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and 54.5% were female. The primary specialty of the great majority of the ICU physicians was anesthesiology (88.2%), followed by internal medicine (9.9%) and surgery (1.9%).…”
Section: Resultsmentioning
confidence: 99%
“…DNI orders entered into the clinical practice at about the same time as DNR orders, and usually DNI orders are accompanied by DNR orders [33]. Code status discussions mostly bundle cardiopulmonary resuscitation with intubation in countries where EOL decisions are legal.…”
Section: Plos Onementioning
confidence: 99%
“…A previous study pointed out that do-not-intubate orders were generally accompanied by DNR orders. [38] There were limitations to this study: (1) it was a retrospective study, and there were some incomplete data in the electronic medical records; (2) the relatives' satisfaction levels and emotional state regarding the quality of care in the ED could not be measured; (3) it was performed in a single academic hospital, and the results may not be representative of the general situation in the Chinese mainland.…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that resuscitation status was associated with specific patient characteristics and our study findings that age, comorbidities and functional independence influence resuscitation status resemble those of other studies. A number of studies have shown that patients with LOMT or not-for-CPR orders are more likely to be older, female and have multiple comorbidities (Jäderling et al, 2013, Jones et al, 2012a, Stream, Nolan, Kwon, & Constable, 2018. Other patient characteristics associated with LOMT or not-for-CPR orders are hospitalisation in the preceding six months (Stream et al, 2018), admission under a medical unit (Jones et al, 2012a), living in residential aged care or supported accommodation (Jones et al, 2012a) and hospital admission for an acute event (Jäderling et al, 2013).…”
Section: Discussionmentioning
confidence: 99%